Shackles on education revamp - Abd Razak, Dzulkifli (2009)
Bologna Process it was a time to celebrate too. The Bologna Process, which started a decade ago with only 29 ministers participating, has now expanded into an almost allEuropean affair. The 46 participating countries in Louvin exemplified a high degree of cooperation and understanding among the Bologna Process members. The Bologna Declaration was signed on June 19,1999 in Bologna, hence the name The Process now stands as a symbol of a successful European reform process aimed at establishing a European Higher Education Area by next year.